Copper, zinc, mercury and arsenic content in Micropogonias furnieri and Mugil platanus of the Montevideo coastal zone, Río de la Plata - Diego Corrales; Alicia Acuña; María Salhi; Gustavo Saona; Ernesto Brugnoli (Brazilian Journal of Oceanography, 2016)
Abstract Metals (Cu, Zn, Hg) and metalloid (As) concentrations were measured in Micropogonias furnieri and Mugil platanus caught in three areas along the Montevideo coastal zone during winter 2010, spring 2010 and 2011. Compared to previous studies conducted in the zone, both species showed higher (for Cu), similar (for Zn) or lower (for Hg) concentrations. The highest Hg values were found in the M. furnieri of Montevideo bay. There was no spatial variation in Cu, Zn, and As concentrations in muscle, likely due to the high mobility of both species. However, the Cu content in the liver of M. furnieri was higher in fish from the West zone. Cu, Zn and As found in the liver of M. platanus were much higher than in that of M. furnieri. A functional relationship between muscle levels of Zn and Hg and fish length of M. furnieri indicates bioaccumulation of these metals. According to the results, M. furnieri may be used as a temporal bioindicator for Hg, but not as a spatial bioindicator. Mercury levels were below the maximum safety level based on international standard values for human consumption.